2008
DOI: 10.1103/physrevb.78.174403
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostatic dipolar domain-wall pinning in chains of permalloy triangular rings

Abstract: In a combined experimental and numerical study, we investigated the details of the motion and pinning of domain walls in isolated and interacting pennalloy triangular rings (side 2 /Lm, width 250 nm, and thickness 25 nm). To induce interaction between the rings, they were arranged either in vertical chains with an apex of each triangle in proximity to the edge center of the triangle above it or in horizontal chains where the proximity is between the adjacent corners of the triangles. Using longitudinal and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…17 All previously reported analyses on the switching of the polarity of the vortex core is devoted to the circular dots where the chirality is not visible by magnetic force microscopy ͑MFM͒ and cannot be controlled. Alternatively, it has been reported that in circular dots with truncated edges and other certainly complex engineered defects, [18][19][20][21][22][23][24][25] the nucleation point of the vortex could be controlled. This allows a possibility of additional control of vortex chirality.…”
Section: Introductionmentioning
confidence: 99%
“…17 All previously reported analyses on the switching of the polarity of the vortex core is devoted to the circular dots where the chirality is not visible by magnetic force microscopy ͑MFM͒ and cannot be controlled. Alternatively, it has been reported that in circular dots with truncated edges and other certainly complex engineered defects, [18][19][20][21][22][23][24][25] the nucleation point of the vortex could be controlled. This allows a possibility of additional control of vortex chirality.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the downward peak observed in the rst branch of the loop in correspondence of the VS is turned to upward in the reverse branch due to the change of VS chirality. In the H conguration, the measured H 1, and H 2, values are smaller than those recorded for non-interacting MNs of ≈ 20 Oe and ≈ 80 Oe, respectively [3]. Beyond that, the sequence of states explored by the MNs during the reversal process is not aected by magnetostatic interactions.…”
Section: Resultsmentioning
confidence: 82%
“…In an earlier work, we studied the eects of dipolar interactions between two adjacent corners, viz. two DWs [3], and we found that interactions induced a change in switching elds values. In this paper, we investigate a dierent conguration, namely the rings are ordered in a hexagonal pattern (see Fig.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…To date, there are many reports on the static behavior of magnetic rings including circular [8][9][10], elliptical [11], triangular [12,13], square [14,15], rhombic [16], rounded rectangular [17,18], and rectangular rings [19]. The effect of ring dimensions [20][21][22], shapes [19,23], inter-ring spacing [24,25], configurational anisotropy [11,26,27], and engineered defects [28,29] on static reversal of the rings have also been examined. In contrast, reports on dynamic behavior of ring elements have focused on the investigation of circular ring [30][31][32][33] and limited work on other ring shapes such as rounded rectangular [34] and triangular rings [35].…”
Section: Introductionmentioning
confidence: 99%